SINGLE MASTER – MULTIPLE SLAVES MICROCONTROLLER IMPLEMENTATION FOR SENDING AND RECEIVING DATA ON WEATHER STATION PROTOTYPE - Dikdik Krisnandi; Purnomo Husnul Khotimah (Widyariset, 2017)
We have carried out the microcontroller research implementation as a Master to control multiple Slaves microcontroller on weather station prototype. Master Microcontroller could be interconnected with four Slaves microcontrollers Slaves, in which each has a different type of input. In this research, we used an ATmega8535 microcontroller. To distinguish between a Slave microcontroller and another Slave microcontroller, an addressing system (ID) is used. Data communication used a standard serial port RS-232 and RS-485 ports, the connector is used to connect the two ports. The Single Board Controller (SBC) Master serves user commands from users, sending the commands and processing Slaves. User commands are given via the keypad and then transmitted using a Universal Asynchronous Receiver-Transmitter (USART) to SBC Slaves. The process on the SBC Slaves is waiting for orders from the Master. The order is detected using an interrupt. After that, the commands are processed and the respond is sent to the SBC Master via USART. When there is no command, Slaves do the idle process. The result shows that the microcontroller application single Master - multiple Slaves has functioned for sending and receiving data in accordance with the specified command. This is shown by the output on a display that has shown the result as expected. The power consumption of each SBC is relatively small which is 0,745 Watt. Thus, it makes the system more economically profitable.